2017
DOI: 10.21873/anticanres.11519
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Surgery – A Population-based Registry Study

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Querleu et al studied 1,000 gynecologic cancer patients who underwent laparoscopic pelvic and/or para-aortic lymphadenectomies [ 21 ]. The intra-operative and early post-operative complication rates, as well as the lymphocyst formation rate were 2.0% and 2.9%, respectively [ 20 ]. Although laparoscopic lymphadenectomy is considered safe, laparoscopic equipment is available in only some tertiary hospitals due to a lack of financial support; hence, 89% of this population underwent exploratory laparotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Querleu et al studied 1,000 gynecologic cancer patients who underwent laparoscopic pelvic and/or para-aortic lymphadenectomies [ 21 ]. The intra-operative and early post-operative complication rates, as well as the lymphocyst formation rate were 2.0% and 2.9%, respectively [ 20 ]. Although laparoscopic lymphadenectomy is considered safe, laparoscopic equipment is available in only some tertiary hospitals due to a lack of financial support; hence, 89% of this population underwent exploratory laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Franchi et al reported a post-operative complica- tion rate of 33.8% (45/133) in endometrial cancer patients [17]. The post-operative complication rate of ovarian cancer patients, depending on the extension of surgical procedures, ranged from 13.3% to 29.9% [18][19][20]. In our subgroups analysis, the overall complication rates in cervical cancer, endometrial cancer and ovarian cancer patients were 39.5%, 29.9% and 59.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, hospital-registry data enabled a greater depth of analysis and greater clinical insights than was possible with population-based registry data that generally exclude data on stage, other prognostic and treatment characteristics. Ideally, hospital-registry data would be extended to cover the entire population, as in Sweden 26. Increased interest exists in recording cancer stage in population-based registries and linking these data to inpatient and health insurance treatment data in Australia 27.…”
Section: Discussionmentioning
confidence: 99%